Factors Associated with Utilization of Insecticide-Treated Nets in Children Seeking Health Care at a Ugandan Hospital: Perspective of Child Caregivers - Nankinga, Ziadah; Kanaabi Muliira, Joshua; Kalyango, Joan; Nankabirwa, Joaniter; Kiwuwa, Steven; Njama-Meya, Denise; Karamagi, Charles (Journal of community health, 2012)
In Uganda malaria causes more morbidity and mortality than any other disease and children below 5 years contribute the biggest percentage of malaria related mortality. Insecticide treated nets (ITNs) are currently one of the most cost effective option for reducing malaria-related morbidity and mortality, however the factors affecting their utilization in Uganda are still not well understood. This study examined the prevalence and factors associated with ITN utilization among children of age 0–12 years seeking health care from a Ugandan hospital using caregiver’s reports. A cross sectional design was used to collect data using a semi-structured questionnaire from 418 participants. Binary logistic regression was employed to determine predictors of ITN utilization. Results show that the prevalence of ITN utilization among children seeking health care was 34.2%. ITN utilization was higher among children of age \5 years [37.0, 95% CI 31.81–42.21] as compared to children aged C5 years [22.9, 95% CI 13.77–32.01]. Source of mosquito net (OR = 13.53, 95% CI = 6.47–28.27), formal employment by head of household (OR = 6.00, 95% CI = 1.95–18.48), sharing a bed with parent (s) (OR = 2.61, 95% CI = 1.21–5.63) and number of children below 12 years in a household (OR = 0.80, 95% CI = 0.65–0.99), were significant predictors of utilization. ITN utilization among children was below the set national target. The predictors identified by this study reveal opportunities that can be taken advantage of by malaria control programs to achieve the desired rates of utilization and subsequently malaria prevention in children.
Keywords: Children; Malaria prevention; Insecticide treated nets; Utilization; Caregivers